Communication Methods of Drug Dealers and Their Impact on Youth in Baghdad - Sanad, Mustafa Amer (ALBAHITH ALALAMI, 2025)
Objectives: This study aims to identify the communication methods used by drug dealers in Baghdad, understand the reasons and factors leading to drug abuse among youth, analyze the language and persuasive techniques used to entice young people into drug use, and highlight the psychological, social, and economic impacts resulting from these methods.Methodology: The study adopted a qualitative exploratory approach, using in-depth interviews as the primary data collection tool. The purposive sample consisted of 15 participants, including drug dealers, drug users, as well as specialists such as anti-narcotics officers, psychiatrists, and journalists. The interviews were analyzed to monitor communication methods and interpret their impacts.Results: The findings revealed that traditional social relationships remain the most prominent channel for drug promotion. Emotional and psychological vulnerability is among the key factors exploited to attract users. The study also found that the transition from drug user to dealer represents a critical stage influenced by these communication tactics. The research concluded that comprehensive preventive approaches are necessary, focusing on community education, enhancing family supervision, and reinforcing security measures.Conclusion: The study uncovered complex communication dynamics used to lure youth into drug use, primarily based on exploiting trust and social ties. Despite the widespread use of technology, traditional methods remain the most effective in the Iraqi context. This requires a multidimensional national preventive strategy that combines family awareness, security enforcement, and psychological and social support for young people.